Why institutional environments for agroforestry seed systems matter. (15th November 2017) - Lillesø, J.P.B.; Harwood, C.; Derero, Abayneh; Graudal, L.; Roshetko, J. M.; Kindt, R.; Moestrup, S.; Omondi, W. O.; Holtne, N.; Mbora, A.; van Breugel, P.; Dawson, I. K.; et al.
Abstract: Rethinking the logic of institutional environments aiming to facilitate agroforestry smallholders in economic development, this article compares smallholder input supply systems for crop and tree seeds in sub‐Saharan Africa and reflects on two basic challenges: (1) how to develop a large number of relevant tree crops for different agroecologies, (2) how to reach smallholders in rural areas. Policy options for improving agroforestry input supply systems are discussed, whereby our article concludes with suggestions how sectoral approaches for crop seed systems can be modified to agroforestry seed‐seedling systems. Biophysical differences have practical implications for how the logic of the 'African green revolution' would be translated into a corresponding revolution for agroforestry.